2014
DOI: 10.1007/s12094-014-1251-1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational trophoblastic neoplasia: treatment outcomes from a single institutional experience

Abstract: GTNs have excellent prognosis if properly treated at experienced centers. Single-agent dactinomycin seems more effective for low-risk GTN. EMA-CO remains the preferred primary treatment regimen for high-risk group. The excellent outcome reflects the success of salvage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 15 publications
7
28
0
Order By: Relevance
“…Our study confirms the lower outcomes in patients with advanced-stage disease, metastatic disease and high-risk prognostic score [11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study confirms the lower outcomes in patients with advanced-stage disease, metastatic disease and high-risk prognostic score [11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 86%
“…A randomized clinical trial compared biweekly Dactinomycin versus weekly Methotrexate demonstrated a superior response rate for Dactinomycin over Methotrexate (69 vs. 53% ; p = 0.015) [9]. Retrospective reviews of patients with low-risk GTN treated with single-agent chemotherapy showed significantly higher primary remission rate with Dactinomycin than with Methotrexate regimen [10,11]. Due to decreased cost and the good tolerance of Methotrexate, especially for not inducing hair loss, Methotrexate was preferred as first line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by its reliance on hematogenous dissemination for metastasis, GC generally spreads to the lungs, liver, central nervous system (CNS) and vagina . This feature is also partially responsible for the high malignancy rate and resistance to chemotherapy of GC, for which the detection of metastasis would be highly valuable for evaluating disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Our results report that the composition of antecedent pregnancy of the patients with CCA has no obvious change in the past 15 years. Most patients developed IM within 6 months after previous pregnancy, especially within 2 to 3 months.…”
Section: Discussionmentioning
confidence: 60%